Synergistic effect of Gr and CNTs on preparing ultrathin Cu-(CNTs+Gr) composite foil via electrodeposition. (15th April 2020) - Song, Gongsheng; Sun, Li; Li, Sishi; Sun, Yafei; Fu, Qiang; Pan, Chunxu
Abstract: The incorporation of nano-reinforcement, such as carbon nanotubes (CNTs) and graphene (Gr), into copper (Cu) matrix via electrodeposition is a promising method to improve its comprehensive property. However, the challenge is to achieve an uniformly suspended electrolyte with these reinforcements or surfactant due to their inferior dispersibility. In this paper, we report a process to produce a kind of high performance Cu-(CNTs+Gr) composite foil by using hybrid self-dispersing reinforcement CNTs+Gr via a direct current (DC) electrodeposition, which further results in an ultrathin foil reach to the thickness as low as 4 μm. In this process, firstly, the precursor graphene oxide (GO) with amphipathicity acts as a surfactant-like substance, and disperses CNTs uniformly through the π-π bonding in-between GO and CNTs in the copper sulfate electrolyte. Then, GO is reduced into Gr during electrodeposition, and the synergistic effects of CNTs and Gr play a key rule to improve the ultrathin Cu-(CNTs+Gr) composite foil's properties, including tensile strength up to 436 MPa, inoxidizability and superior electrical conductivity, This work provides a possibility to have mass-production of Cu foil as thin as 4 μm in industry and broad applications in the future.